2021
DOI: 10.1108/jsfe-02-2021-0007
|View full text |Cite
|
Sign up to set email alerts
|

Flexural behavior of fire damaged self-compacting concrete beams strengthened with fiber reinforced polymer (FRP) wrapping

Abstract: PurposeBuilding elements that are damaged by fire are often strengthened by fiber wrapping techniques. Self-compacting concrete (SCC) is an advanced building material that is widely used in construction due to its ability to flow and pass through congested reinforcement and fill the required areas easily without compaction. The aim of the research work is to examine the flexural behavior of SCC subjected to elevated temperature. This research work examines the effect of natural air cooling (AC) and water cooli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Moreover, the nature of cooling significantly affects the strength loss of all the beam specimens. All the watercooled beam specimens showed efficient performance compared to air-cooled beam specimens, similar trend in the results were observed by Mathews et al [4].…”
Section: Ultimate Load-carrying Capacity Of Beam Specimenssupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, the nature of cooling significantly affects the strength loss of all the beam specimens. All the watercooled beam specimens showed efficient performance compared to air-cooled beam specimens, similar trend in the results were observed by Mathews et al [4].…”
Section: Ultimate Load-carrying Capacity Of Beam Specimenssupporting
confidence: 89%
“…Many researchers have conducted detailed study on the physical and strength performance of concrete and FRP reinforcement steel under elevated temperatures. When concrete is exposed to a higher temperature, the weight loss, deformation changes in aggregate and damage of CSH gel, chemical changes, spalling, and decreases in mechanical properties occurs and lead to deterioration of the structural members [4]. Yield strength, ultimate strength, and modulus of elasticity of steel materials degrade when subjected to high temperatures [5].…”
Section: Introductionmentioning
confidence: 99%
“…Through numerical simulations, it was demonstrated that the fire resistance of structures is significantly affected by the duration and intensity of exposure, as well as by the materials used. Therefore, [3] investigated the exposure to high temperatures in conventional reinforced concrete structures and their loss of strength under heat. For this reason, the implementation of carbon fibers was proposed.…”
Section: Introductionmentioning
confidence: 99%
“…This concludes that carbon fiber reinforced beams are the best option to achieve greater flexural strength under high temperature conditions. In previous studies [3,4], the mechanical properties of high-strength concrete reinforced with hybrid steel and polypropylene fibers were evaluated after exposure to different temperatures. The results showed a decrease in both compressive and flexural strength with increasing temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Fire disasters can occur under or on the ground and sometimes in the most unexpected circumstances and considered one of the most serious potential disasters for most structures [1]. The widespread use of concrete as a building material has led to the need for a comprehensive understanding of fire effects and strengthening of affected concrete structures [2].…”
Section: Introductionmentioning
confidence: 99%